Kopalnia węgla brunatnego "Borussia" koło Ośna Lubuskiego = Lignite mine "Borussia" near Ośno Lubuskie, West Poland - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents history of lignite mining in region of Ośno Lubuskie (north west part of Ziemia Lubuska -West Poland). It describes underground mining in complicated geological condition (glaciotectonic deformations). The paper is based on remained German archival materials (Main Mining Office) and also some Polish materials. The paper also describes the discovery of lignite deposits in the nineteenth century, as well as the detailed history of one of the largest mines in the region, i.e. "Borussia" in Trześniów. The paper is supplemented with historical maps showing the locations of the mines and presents the available technical and statistical data.
Keywords: górnictwo węgla brunatnego; podziemna eksploatacja; górnictwo - historia; lignite mining; underground exploitation; mining history; Ośno Lubuskie